Differential response to acidic pH in rice seedlings - Jay Prakash Awasthi; Bedabrata Saha; Bhaben Chowardhara; Pankaj Borgohain; Smita Sahoo; Bhaben Tanti; Sanjib Kumar Panda (Universitas Sebelas Maret, 2022)
Acidic soil is a serious harmful problem for rice crop productivity. Approximately 50% of the world’s potentially arable soils are acidic, whereas in North East (NE) India 80% of arable soils are effected. In nature, it exists synergistically with other metal stresses. Hence most of the studies to date were performed in combinations. This paper highlights the detrimental effect of acidity on plants to differentiate between the effect of acidity on plant growth to that of stress in combinations. We depict it through a cascade of morphological and physiological assays, including growth, reactive oxygen species (ROS), and photosynthesis-related parameters under acidic and non-acidic rhizospheric conditions in rice seedlings of Disang and Joymati. Up to 31% root length reduction was observed in Joymati, and up to 17% reduction in Disang variety; whereas, root-relative water content was observed to reduce by 3% in Disang and 9% was recorded in Joymati cultivars. Overall, we observed limited effect on morphometric parameters like root length, biomass, and chlorophyll content irrespective of variety analyzed. On the contrary, ROS accumulation was observed to be significantly increased; more in Joymati (sensitive variety) when compared to Disang (tolerant variety). Although there was not much decrease in chlorophyll content, photosynthesis was affected immensely as depicted from chlorophyll fluorescence parameters. Hence through this study, we hypothesize that the response of plants to acid stress is rather slow.